Migraine and obesity: metabolic parameters and response to a weight loss programme. Issue 3 (3rd July 2014) - Verrotti, A.; Carotenuto, M.; Altieri, L.; Parisi, P.; Tozzi, E.; Belcastro, V.; Esposito, M.; Guastaferro, N.; Ciuti, A.; Mohn, A.; Chiarelli, F.; Agostinelli, S.
Summary Background and objective Weight loss can determine significant improvement of migraine in obese patients. Herein, we evaluated a clinical sample of adolescent migraineurs with obesity who participated in an interdisciplinary programme for weight loss, in order to identify possible metabolic parameters associated with good migraine control. Subjects and methods Using a cross‐sectional design, we evaluated 112 out of 135 adolescents who previously underwent our intervention programme. Based on persistence of headache, subjects for comparison were 40 migraine‐free and 72 not migraine‐free adolescents. Participants underwent anthropometric evaluations and biochemical tests. Results Patients with persistence of migraine had significantly higher weight (P < 0.01), body mass index (P < 0.01), waist circumference (P < 0.01), homeostasis model assessment of insulin resistance (P < 0.001), triglyceride (P < 0.05), total cholesterol (P < 0.05) and low‐density lipoprotein cholesterol (P < 0.05) values when compared with those who became migraine‐free. Between potential predictors, only insulin resistance (odds ratio = 3.5, 95% confidence interval = 1.4–6.1; P < 0.001) was significantly associated with persistence of migraine after intervention programme. Conclusions Among obese adolescents with migraine who underwent an intervention programme for weight loss, patients who did not become migraine‐free showed higher adiposity values than those who became migraine‐free. Patients with insulin resistance had 3.5 times the odds of having persistence of migraine compared with those without.